Solution of Dynamic Optimization Problems Constrained by the Fraction Penalty Method - Hartono, Hartono (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2020)
This article discusses the application of fractional penalty method to solve dynamic optimization problem with state constraints. The main theories supporting the use of the method are described in some theorem and corollary. The theorems give sufficient conditons for the application of the method. Therefore, if all conditions mentioned in the theorems are met then the resulted solution will converge to the analytic solution. In addition, there are some examples to support the theory. The numerical simulation shows that the accuracy of the method is quite good. Hence, this method can play a role as an alternative method for solving dynamic optimization problem with state constrints.